2013
DOI: 10.1038/cddis.2013.270
|View full text |Cite
|
Sign up to set email alerts
|

Anti-androgen receptor ASC-J9 versus anti-androgens MDV3100 (Enzalutamide) or Casodex (Bicalutamide) leads to opposite effects on prostate cancer metastasis via differential modulation of macrophage infiltration and STAT3-CCL2 signaling

Abstract: Despite androgen deprivation therapy (ADT) suppression of prostate cancer (PCa) growth, its overall effects on PCa metastasis remain unclear. Using human (C4-2B/THP1) and mouse (TRAMP-C1/RAW264.7) PCa cells–macrophages co-culture systems, we found currently used anti-androgens, MDV3100 (enzalutamide) or Casodex (bicalutamide), promoted macrophage migration to PCa cells that consequently led to enhanced PCa cell invasion. In contrast, the AR degradation enhancer, ASC-J9, suppressed both macrophage migration and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
150
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(160 citation statements)
references
References 34 publications
8
150
0
Order By: Relevance
“…1C), PKC phosphorylation, and Twist1 protein expression, which was accompanied by a decreased E-cadherin and an increased fibronectin expression (Fig. 1D), consistently with the previous reports on EMT promotion by enzalutamide (27,28).…”
Section: Blocking Ar Signaling Induces Pkc Phosphorylation and Twist1supporting
confidence: 78%
“…1C), PKC phosphorylation, and Twist1 protein expression, which was accompanied by a decreased E-cadherin and an increased fibronectin expression (Fig. 1D), consistently with the previous reports on EMT promotion by enzalutamide (27,28).…”
Section: Blocking Ar Signaling Induces Pkc Phosphorylation and Twist1supporting
confidence: 78%
“…We thus conclude that SOCS3 is not directly regulated by the androgen receptor. Recent publications demonstrated that anti-androgen treatment can enhance STAT3 activity (15,46). Indeed, we could not only confirm an increased STAT3 activation after treatment with enzalutamide but also achieve complete reversal of the effect on SOCS3 by blocking the transcriptional activity of STAT3.…”
Section: Discussionsupporting
confidence: 65%
“…Activated STAT3 has been found in primary as well as in metastatic prostate cancer and correlates with Gleason score, tumor stage, and castration resistance (11,13). Constitutively active STAT3 has been shown to confer enzalutamide resistance (14), and STAT3 has been implicated in promoting metastasis during treatment with the antiandrogens bicalutamide and enzalutamide (15). Furthermore, STAT3 has been shown to bind and trans-activate the N-terminal domain of the AR (7), which may lead to enhanced activation of the androgen receptor and drive progression to castration resistance.…”
Section: Introductionmentioning
confidence: 99%
“…They all inhibit PCa proliferation and reduce PSA levels, but only ASC-J9 was able to suppress cell invasion and thus the formation of metastases in in vitro and in vivo models (Lin et al 2013a). A different modulation of the STAT3-CCL2 signaling pathway was suggested to lie at the base of this observed difference (Lin et al 2013b).…”
Section: Experimental Ar-targeted Therapiesmentioning
confidence: 99%